The growth success of Alstonia scholaris (L.) R. Br. shoot cuttings from several shoots position and the cut type of cuttings - Mashudi; Hamdan Adma Adinugraha (Jurnal Penelitian Kehutanan Wallacea, 2015)
Alstonia scholaris (L) R.Rr. is one of the fast growing species has a wide distribution in Indonesia and good prospect to be developed for forest plantation. This species could be propagated both generative and vegetative method. This study was conducted to identify the effect of shoot position and the cut type of cuttings. The experiment was arranged in Randomized Complete Design in two factors. The fisrt factor was shoot position (P1= < 50 cm, P2=50-100 cm, P3=100-150 cm and P4=150-180 cm above ground) and second was the cut type of cuttings (horizontal, diagonal 45o and “V” types). The result showed that shoot position significantly influenced rooting ability and the growth of cuttings. The best result of shoot cuttings was taken from P3 treatment (100-150 cm above ground) with survival percentage 87.50%, rooting percentage 85.42%, growth of height 4.02 cm, with 10 number of root, length of root 19.08 cm and 4 number of leaf . The cut type of cuttings and interaction between shoot position and type of cuttings were not significantly differences to the growth of shoot cuttings.